2002
DOI: 10.1001/archopht.120.7.923
|View full text |Cite
|
Sign up to set email alerts
|

Postenucleation Adjuvant Therapy in High-Risk Retinoblastoma

Abstract: The main purpose of this study was to determine the efficacy of postenucleation adjuvant therapy in preventing metastasis in cases of high-risk retinoblastoma. Methods: This was a retrospective, nonrandomized comparative study. Of 1020 consecutive patients with retinoblastoma had were managed at a referral center between January 1974 and December 1999, 80 (8%) of those analyzed had unilateral sporadic cases that were treated by primary enucleation and that had high-risk characteristics for metastasis on histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
186
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(191 citation statements)
references
References 33 publications
3
186
1
1
Order By: Relevance
“…Those at greatest risk for metastasis show features of retinoblastoma invasion beyond the lamina cribrosa in the optic nerve, in the choroid (>2 mm dimension), sclera, orbit, or anterior chamber. 13 Eyes with invasion of the optic nerve or choroid generally demonstrate large retinoblastoma over 15 mm greatest dimension along with elevated intraocular pressure and total retinal detachment. 14,15 Patients with evidence of invasive retinoblastoma should be treated with chemotherapy for 4 to 6 months to prevent metastases; however, criteria for regarding the need for adjuvant chemotherapy remain unclear.…”
Section: At Risk For Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Those at greatest risk for metastasis show features of retinoblastoma invasion beyond the lamina cribrosa in the optic nerve, in the choroid (>2 mm dimension), sclera, orbit, or anterior chamber. 13 Eyes with invasion of the optic nerve or choroid generally demonstrate large retinoblastoma over 15 mm greatest dimension along with elevated intraocular pressure and total retinal detachment. 14,15 Patients with evidence of invasive retinoblastoma should be treated with chemotherapy for 4 to 6 months to prevent metastases; however, criteria for regarding the need for adjuvant chemotherapy remain unclear.…”
Section: At Risk For Metastasismentioning
confidence: 99%
“…In an analysis from our department, metastases were reduced from 24% in those without preventive chemotherapy to 4% in those with chemotherapy. 13 …”
Section: At Risk For Metastasismentioning
confidence: 99%
“…The significance of isolated anterior segment involvement remains debatable, but we have previously witnessed metastasis in such cases, so this was included as a factor. 10 Some authors 5,13 have suggested that anterior segment involvement and isolated choroidal invasion are not risk factors for metastasis. The other major source of variation is related to the definition of massive choroidal invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Uusitalo and associates 31 studied 129 patients using variable regimens and concluded that chemoprophylaxis was beneficial in patients with tumor extending beyond the lamina cribrosa. Honavar and colleagues 10 conducted a retrospective, nonrandomized comparative study of 80 patients with high-risk RB, in which 58% of patients received adjuvant therapy and 42% did not receive adjuvant therapy for various reasons. A significant difference was found in the rate of metastasis between the group that had received adjuvant therapy (4%) and the group that had not (24%).…”
Section: Discussionmentioning
confidence: 99%
“…38,[43][44][45] High-risk retinoblastoma leads to metastasis in 24% of patients if not treated with systemic chemotherapy compared with 4% of those that receive IVC. 44 The International Classification of Retinoblastoma can predict those eyes with high-risk retinoblastoma. It is presumed that groups A, B, and C rarely show high-risk features, but they rarely come to enucleation for histopathological inspection.…”
Section: Prevention Of Systemic Metastasis In High-risk Retinoblastomamentioning
confidence: 99%